2014
DOI: 10.1002/mana.201400192
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrisers and generalised solutions for strictly hyperbolic systems with singular coefficients

Abstract: This paper is devoted to strictly hyperbolic systems and equations with non-smooth coefficients. Below a certain level of smoothness, distributional solutions may fail to exist. We construct generalised solutions in the Colombeau algebra of generalised functions. Extending earlier results on symmetric hyperbolic systems, we introduce generalised strict hyperbolicity, construct symmetrisers, prove an appropriate Gårding inequality and establish existence, uniqueness and regularity of generalised solutions. Unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In case of systems or higher order equations, an incoming singularity will split at the interface into a refracted and a reflected wave. While in many cases it has been shown that the Colombeau solution is associated with the distributional solution of the transmission problem [13,20], the task of identifying the refracted and reflected singularity by means of the Colombeau wave front set -directly in the generalized solution without considering the associated distribution -has remained open.…”
Section: Introductionmentioning
confidence: 99%
“…In case of systems or higher order equations, an incoming singularity will split at the interface into a refracted and a reflected wave. While in many cases it has been shown that the Colombeau solution is associated with the distributional solution of the transmission problem [13,20], the task of identifying the refracted and reflected singularity by means of the Colombeau wave front set -directly in the generalized solution without considering the associated distribution -has remained open.…”
Section: Introductionmentioning
confidence: 99%
“…The proofs of solvability are based on refined energy estimates on lens-shaped regions with spacelike boundaries. We obtain several variants and also partial extensions of previous results in [26,23,16] and provide aspects accompanying related recent work in [28,10,9]. MSC 2010: 46F30; 35L45, 35D30 Keywords: generalized functions, generalized solutions to hyperbolic systems * The author acknowledges the support of FWF-project grants Y237 and P20525.…”
mentioning
confidence: 65%
“…Yet this concept of regularity is restricted to situations where distributional limits exist and therefore not applicable if initial data or right-hand side are not associated to any distribution. Intrinsic regularity theory in Colombeau algebras is based on the subalgebra G ∞ (Ω) of regular generalized functions in G(Ω) and has been investigated in the context of hyperbolic partial differential equations in [21,19,28,10,9]. In the study of intrinsic regularity of generalized solutions to partial differential equations, the notion of slow scale nets was introduced in [20] and has proven to be essential in many circumstances (cf.…”
Section: Regularity Of the Generalized Solutions And Distributional Lmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory of generalized solutions to linear hyperbolic first-order systems has been developed over 20 years and has achieved a spectrum of results on existence and uniqueness of solutions to the Cauchy problem, distributional limits and regularity of solutions, and symmetrizability (cf. [Obe89,Obe92,LaOb91,Obe09,HoSp12,GaOb11b]). On the other hand, generalized solutions of wave equations arising via the Laplace-Beltrami operator of a Lorentzian metric of low regularity have been studied in [ViWi00, May06, GMS09, Han11, HKS11].…”
Section: Introductionmentioning
confidence: 99%